Workplace deviant behaviour among employees in the Malaysian luxury hotels - Ali Mahamad, Amirah Sayeedah (2020)
Hotel industry is one of the largest industries in service sector that contributed to the growth of economy in Malaysia. The major key factor that influences the success in this industry is the service quality which delivered by the hotels’ employees. Therefore, a study of the behaviour among the employees in hotel industry was carried out to serve as one of the efforts to help Human Resource Department to cater this issue, thus automatically improve the quality of service deliver by employees. This paper is aim to study the workplace deviant behaviour among employees in Malaysian hotel industry. Workplace deviant is the intentional behaviour that interrupts organisational norms or culture. In order to tackle this issue, this study first approached is to identify the level of deviant act demonstrated by the employees of the hotel industry in Malaysia. The factors that influence the deviant act in workplace are organisational-related factors and work- related factor. Job satisfaction became the mediating effect that influence for both factors, organisational-related factors and work-related factors. The research quantitative research as the methodology used to discover the final result in this study. As this study is related to hotel industry, hence the respondent for this study is the employees in 5 star hotels in Malaysia which listed under the Malaysian Association of Hotels (MAH) and was randomly selected according to states. To analysis the data the researcher used smart PLS 3.0 and SPSS version24.0and the researcher has conducted the pilot study with 30 employees in the Malaysian hotel industry in order to test the reliability of the instrument. The final results show that the organisational factors such as organisational justice, perceived organisational support and organisational constrains do influence workplace deviance among the employees in the hotel industry. While the workplace-related factor such as work stress and job autonomy has a low influence towards workplace deviance among the employees in the hotel industry in Malaysia. Job satisfaction is needed as the mediating effect as the lack or low level of satisfaction will lead to workplace deviant among employees.